PENYULUHAN DAN PENDAMPINGAN TENTANG STRATEGIC PLAN KAMPUNG HERITAGE KAYUTANGAN DENGAN PRODUCT DIVERSIVICATION - Bunyamin Bunyamin; Siti Munfaqiroh; Dwi N A; Sugeng H; Nunung N U; Imama Z; Setiawan Setiawan; Nanang P (Jurnal Pengabdian kepada Masyarakat, 2020)
One of the efforts to develop the Kajoetangan heritage village of Malang is the development of product diversification. This is an effort that can be developed in order to find a unique heritage village of Kajoetangan, Malang city with other tourist villages in Indonesia. This form of diversification is the buildings of ancient houses that can be fixed so as to present the atmosphere of the Dutch colonial era to visitors to this tourist village.In addition to buildings, it also presents old products that can support this, such as ancient chandeliers, old moped, vintage motorbikes, as well as old furniture and household items.Supporting the product diversification is a strategic plan for culinary centers or traditional hawker sellers carried out by local residents so as to support the colonial era nuance to visitors of the Kajoetangan heritage village of Malang city.Another supporter of this diversification is the strategic plan for the center for selling souvenirs typical of the Kajoetangan heritage village in the form of t-shirts with Kajoetangan heritage images, old-style lurik clothes, Malangan blangkon, and other souvenirs. This will make the characteristic of a wooden heritage village that distinguishes it from other tourist villages. This is a good strategic plan for the development and promotion of media for the Kajoetangan heritage villageStrategy Plan for Diversification of tourism products that do not exist in other tourist villages in Malang and other cities in Indonesia. The photo spot is a tourist destination for existing visitors. To be able to upload photos on social media owned. So that the resulting output is the Strategic Plan of the Kajoetangan Heritage Village with Product Diversivication